Atividade de lectinas e metabólitos bioativos de plantas sobre biofilmes microbianos de interesse clínico - Vasconcelos, Mayron Alves de (2013)
Biofilms are microbial communities that are irreversibly attached to a surface and are embedded in a polymeric matrix produced by them. Biofilms are commonly related to nosocomial infections that showing an enhanced resistance to antimicrobial agents compared to planktonic cells, thus hindering their treatments and limiting therapeutic options. In this context, the search for new molecules with antimicrobial and antibiofilm action has become an active area of research. The plants are sources of a variety of molecules with antimicrobial properties, among them we can mention the lectins and secondary metabolites. Several studies have reported the antimicrobial and antibiofilm action of these molecules classes as an alternative to antibiotics. Thus, the aim of this study was to evaluate the antimicrobial and antibiofilm of various lectins isolated from leguminous and algae, as well as two secondary metabolites isolated from plants , derriotusone A (isolated from Lonchocarpus obtusus) and casbane diterpene (isolated from Croton nepetaefolius). The results showed that some lectins tested were able to inhibit the planktonic growth and/or the biofilm formation of certain microorganisms. The lectin isolated from Vaitarea macrocarpa (VML) showed to be the most promising lectin, showing strong action on the planktonic growth and biofilm formation of Staphylococcus aures and Staphylococcus epidermidis. The derriobstusone A showed potential antibacterial and antibiofilm activite on S. aureus, whereas Escherichia coli showed lower sensitivity to the compound. In addition, derriotusone showed a potential antioxidant activity. Regarding to casbane diterpene, in general the compound was able to inhibit planktonic growth, formation of biofilms and disrupt the preformed biofilms of the S.aures, S. epidermidis, Candida albicans and Candida glabrata, and also showed to be effective against biofilms formed by the association between these bacteria and yeasts. In conclusion, the results showed that some lectins, as the secondary metabolites used in this study, may be considered as potential antimicrobial and antibiofilm agents, thus suggesting the use of these molecules in the treatment of infections associated with different microorganisms.